Racism And Discrimination In Maria Campbell’s Halfbreed (Journal of Namibian Studies : History Politics Culture, 2023)
Maria Campbell is an outstanding Metis writer and known for her novel Halfbreed (1973). She recounts her experiences being subjected to discrimination from white dominated people and the government. She belongs to the group called Metis who are the mixed people in the society of Canada. They are the combination between the community and group of culture who are discriminated in everywhere in the society. Campbell shows the sorrows of such community through her words and writings. The article gives an idea about Metis people and the vulgarity they faced in the society and in particular, the life of Maria which devastated her dream.